Kinerja Pra Produksi, Proses Produksi, Pasca Produksi Siaran Radio Dakwah Islam - Efendi, Erwan; Arif Sagala, Rodika Sima; Tanjung, Sri Rezeki (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Islam is a da'wah religion, so its adherents are required to always carry out da'wa activities in society. Da'wah activities can be carried out in various ways that do not conflict with Islamic teachings. One way is through electronic mass media such as radio. This research is a field research, which collects data in the field in a systematic and comprehensive manner. So that in carrying out this exploration, it requires creators to go directly to the field to reveal information and realities that occur in a straightforward and impartial manner. From the selected research, it can be seen that the data in this study were collected using the findings of direct observation and interviews. The study findings show that the production procedures carried out have complied with the Broadcasting Operational Standards (SOP) starting from pre-production, production, and post-production at the time of production. Therefore, this research is expected to assist in the process of producing radio programs broadcasting Islamic da'wah and making a theoretical contribution to the advancement of Islamic communication and broadcasting. Keywords: Radio, Da'wah, Pre-production, production, and post-production.